Model Aplikasi Edukasi Mengenal Hewan Berbantuan Augmented Reality - Akhmad Zakirin; Setyo Wahyu Saputro; Wahyudi Ariannor (STMIK Banjarbaru, 2022)
In the process of learning to recognize animals, many animal objects are difficult to find in the Early Childhood environment, so that learning to recognize animal objects experiences obstacles. There are many students who find it difficult to distinguish animal objects, especially those that have similarities. Augmented Reality-based application models for animal recognition education will be applied to the teaching and learning process. The Multimedia Development Life Cycle method is used to develop the system. System design uses the Unified Modeling Language (UML) modeling tools, while system development uses the Vuforia library, and functional testing uses the Blackbox test. The Augmented Reality-based application model for animal recognition education helps teachers in children's cognitive learning to provide children with an understanding of natural concepts around animal recognition, and can attract interest in learning and increase children's natural intelligence.Keyword: Recognition; Virtual; Cognitive; Natural Intelligence AbstrakPada proses belajar mengenali hewan, banyak objek hewan yang sulit ditemui di lingkungan Anak Usia Dini, sehingga pembelajaran mengenali objek hewan mengalami kendala. Terdapat banyak peserta didik yang merasa kesulitan dalam membedakan objek hewan, terutama yang memiliki kemiripan. Model aplikasi berbasis Augmented Reality untuk edukasi pengenalan hewan, akan diterapkan untuk proses belajar mengajar. Metode Multimedia Development Life Cycle digunakan untuk mengembangkan sistem. Desain sistem menggunakan tools pemodelan Unified Modelling Language (UML), sedangkan pembangunan sistem dengn library Vuforia, serta pengujian fungsional dengan uji Blackbox. Model aplikasi berbasis Augmented Reality untuk edukasi pengenalan hewan membantu guru dalam pembelajaran kognitif anak untuk memberi pemahaman anak terhadap konsep alam sekitar pengenalan hewan, serta dapat menarik minat belajar dan meningkatkan kecerdasan natural anak-anak.